Pozycja prawna państwowego Kościoła Szkocji - Zieliński, Tadeusz J. (Czasopismo Prawno-Historyczne, 2010)
The Church of Scotland, alongside the Church of England, is one of the two state, or established churches in Great Britain. The legal status of the Church of Scotland is of particular nature, not encountered in other European states, as it combines a religious institution with public authority. Its present shape was constituted in the Church of Scotland Act 1921 and followed an agreement it concluded with the British state. The Church of Scotland enjoys complete independence from the state in spiritual matters and its position is generally more privileged in comparison to that of other religious communities. The latter fact may be criticised by those who postulate equality before the law, and in particular the equal treatment of all religious communities. And yet, the Scottish model seems to find fewer critics than the Church of England model prevailing in England. Therefore, if Great Britain is to experience a revision of the relationship between the public authority and religion, such changes will most probably first happen in the southern part of the UK. Thus the future of the Church of Scotland depends on the developments in the Church of England.